2004
DOI: 10.1073/pnas.0401139101
|View full text |Cite
|
Sign up to set email alerts
|

The Six1 homeoprotein stimulates tumorigenesis by reactivation of cyclin A1

Abstract: Homeobox genes constitute a large family of transcription factors that are essential during normal development and are often dysregulated in cancer. However, the molecular mechanisms by which homeobox genes influence cancer remain largely unknown. Here we show that the tissue-restricted cyclin A1 is a transcriptional target of the Six1 homeoprotein. Both genes are expressed in the embryonic but not the terminally differentiated mammary gland, and Six1-knockout mice show a dramatic reduction of cyclin A1 in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
224
3
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(244 citation statements)
references
References 43 publications
13
224
3
1
Order By: Relevance
“…The multiple mechanisms of Six1 regulation throughout the cell cycle suggest that it is critical to confine the activity of this transcription factor to specific cell cycle stages, where it is expected to play an important role. Indeed, our previous studies in tissue culture cells have demonstrated that Six1 overexpression can alter progression through S phase and also through G 2 /M (Ford et al, 1998;Coletta et al, 2004), times when Six1 activity would be expected to be high. Furthermore, a number of knockout studies in mice have demonstrated a critical role for Six1 in the proliferation of precursor cell populations, leaving no ambiguity about the importance of Six1 in proliferation in vivo (Zheng et al, 2003;Ozaki et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The multiple mechanisms of Six1 regulation throughout the cell cycle suggest that it is critical to confine the activity of this transcription factor to specific cell cycle stages, where it is expected to play an important role. Indeed, our previous studies in tissue culture cells have demonstrated that Six1 overexpression can alter progression through S phase and also through G 2 /M (Ford et al, 1998;Coletta et al, 2004), times when Six1 activity would be expected to be high. Furthermore, a number of knockout studies in mice have demonstrated a critical role for Six1 in the proliferation of precursor cell populations, leaving no ambiguity about the importance of Six1 in proliferation in vivo (Zheng et al, 2003;Ozaki et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that Six1 promotes cell cycle progression (Ford et al, 1998;Coletta et al, 2004), and that Six1 transcript levels and phosphorylation state are regulated in the cell cycle (Ford et al, 1998(Ford et al, , 2000. As the expression of many proteins with cell cycle regulatory functions is controlled by ubiquitin-mediated proteolysis, we asked whether Six1 protein levels were also regulated in a cell cycle-specific manner.…”
Section: Six1 Expression Fluctuates In the Cell Cyclementioning
confidence: 99%
See 2 more Smart Citations
“…6,21 Besides, HDAC5 was reported to boost HCC cell proliferation through upregulation of Six1 which could activate cyclin A1. 22,23 In this study, we noticed that deprivation of HDAC5 impaired the hypoxia-induced migration and invasion of HCC cells; however, no obvious effect of HDAC5 knockdown was observed under normoxia. Meanwhile, HDAC5 overexpression enhanced the malignant phenotypes under hypoxia but not normoxia.…”
Section: Discussionmentioning
confidence: 84%